Pengaruh Tarif Pajak, Pemahaman Perpajakan, dan Sanksi Perpajakan Terhadap Kepatuhan Wajib Pajak UMKM - Cahyani, Luh Putu Gita; Noviari, Naniek (E-Jurnal Akuntansi, 2019)
Micro, Small and Medium Enterprises (SME’s) are one sector that has the potential to contribute to state tax revenue. Taxpayer compliance sector SME’s is very low, especially taxpayer compliance UMKM registered at KPP Pratama Singaraja in 2015-2017 has not reached 50%.The purpose of this study was to test of tax rates, understanding taxation and tax sanctions on SMEs taxpayer compliance. The theory used in this study is the theory of planned behavior. Based on the population, the sample in this study is 100 SMEs taxpayer were selected as respondents using the Slovin formula. The method of determining the sample in this study is accidental sampling and technical data analysis of this study using multiple linear regression analysis. The results show that the tax rate, understanding of taxation and taxation sanctions have a positive effect on SMEs taxpayer compliance. Keywords : Tax rate, understanding of taxation, taxation sanctions, SMEs taxpayer compliance